Cyclosporine A concentrations in blood measured with the immunoassays on Roche e601® and ADVIA Centaur XP® analysers-what is the extent of the agreement? - Tijanić, Aleksandra; Beletić, Anđelo; Stanković, Sanja (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2023)
Monitoring of cyclosporine A (Cs A) concentrations is inevitable for efficient and safe immunosuppression. Currently, immunoassays are the most often used method. The study compared the Cs A concentrations in EDTA-blood samples of 50 patients, measured on Roche e601® and ADVIA Centaur XP® analyzers. The Cs A concentrations on e601® were between 30.00 and 573.00 ng/mL. On Centaur XP® they were in the range 30.2-395.2 ng/mL. For all data the correlation coefficient (95% confidence interval (CI)) was 0.98 (0.97-0.99), while in the groups with concentrations below and above 100 ng/mL it was 0.90 (0.74-0.93) and 0.98 (0.94-0.99), respectively. The slope (95% CI) in the Passing-Bablok analysis on all results was 0.73 (0.67-0.83), and the intercept (95% CI) was 12.53 (6.66-17.78). In the group with results below 100 ng/mL, the slope was 0.92 (0.77-1.12) and the intercept 3.05 (from -8.45 to 12.09). For the Cs A concentrations above 100 ng/mL the slope was 0.71 (0.64-0.84) and the intercept 9.31 (from -8.86 to 24.27). The proportional and systematic errors were present in a wide range of Cs A concentrations measured on the evaluated analyzers. The concordance was satisfactory for concentrations below 100 ng/mL.